Inter-annual variability in blue whale distribution off Southern Sri Lanka between 2011 and 2012 - de Vos, Asha; Pattiaratch, Charitha B.; Harcourt, Robert G. (Journal of Marine Science and Engineering, 2014)
Blue whale (Balaenoptera musculus) movements are often driven by the availability of their prey in space and time. While globally blue whale populations undertake long-range migrations between feeding and breeding grounds, those in the northern Indian Ocean remain in low latitude waters throughout the year with the implication that the productivity of these waters is sufficient to support their energy needs. A part of this population remains around Sri Lanka where they are usually recorded close to the southern coast during the Northeast Monsoon. To investigate inter-annual variability in sighting locations, we conducted systematic Conductivity-Temperature-Depth (CTD) and visual surveys between January-March 2011 and January-March 2012. In 2011, there was a notable decrease in inshore sightings compared to 2009 and 2012 (p <0.001). CTD data revealed that in 2011 there was increased freshwater in the upper water column accompanied by deeper upwelling than in 2012. We hypothesise that anomalous rainfall, along with higher turbidity resulting from river discharge, affected the productivity of the inshore waters and caused a shift in blue whale prey and, consequently, the distribution of the whales themselves. An understanding of how predators and their prey respond to environmental variability is important for predicting how these species will respond to long-term changes. This is especially important given the rapid temperature increases predicted for the semi-enclosed northern Indian Ocean.